Invasive pest species and plant diseases in the south-east of Kazakhstan (Experimental biology, 2020)
The replenishment of the composition of  invasive pest and diseases occurs due to the introduction of  harmful species with planting material and seeds. For the first time in the territory of the MBG such dangerous pests as Parthenolekanium fletscheriCkll., Coleophora laricella Hb. were identified including 25 species of aphids imported by introduced species that have not previously been reported in the Alma-Ata region. Podosphaera pannosa (Wallr.Fr.) de Bary, Golovinomyces magnicellulataU.Braun, Phragmidium disciflorum (Tode) J.James, Erysiphe ornate var.eurapae (U.Braun), Botrytis paeoniae Oudem are announced to be common plant diseases. According to the assessment of the phytosanitary condition of introduced plants in recent years, an increase in the number of penetrating new species of endangering  insects and diseases is observed. Thus, the number of pests in greenhouses has increased to 13 species from Coccoidea and Aphidinea.     In open ground, the significative of new species is counted to be 9. One type of the diseases  (Uncinulaflexuosa Peck.), was imported with planting material, which had not previously been noted in the conditions of the south-east Kazakhstan. In order to reduce the harmfulness of pests and diseases, such preparations as aktelik, keltan, purified 18 с.e. dicofol, Rum and Haas (USA), omayt, 30% w.p., 57 % c.e. eniroyal, USA have been consumed. These preparation are used with 0.2% conc. against ticks, mealybug, Diaspididae and aphids.The assessment of the harmfulness degree was carried out on a three-point scale.     Key words: invasive pests and plant diseases, control measures.